Analisis Penggunaan Teknologi E-Learning Menggunakan Technology Acceptance Model (TAM) pada Mahasiswa Perguruan Tinggi Swasta - Imam Fauzi Akmal; M Hafizh Azhar Ar; Debi Irawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research is motivated by the increasing use of e-learning systems in Indonesian universities post-COVID-19 pandemic, which has accelerated digital transformation in the learning process. Although the implementation of e-learning is becoming increasingly widespread, students' acceptance levels of the system still vary and are influenced by their perceptions of ease of use and perceived benefits. Therefore, this study aims to analyze student acceptance of the e-learning system using the Technology Acceptance Model (TAM) approach, focusing on the influence of Perceived Ease of Use (PEOU) on Perceived Usefulness (PU), as well as the influence of PEOU and PU on Behavioral Intention to Use (BIU). This research uses a quantitative approach with an associative-causal design. The research respondents were 100 active students who had used the e-learning system for at least one semester, selected thru purposive sampling. Data was collected online using a closed questionnaire and analyzed using simple linear regression and multiple linear regression techniques. The research findings indicate that PEOU has a positive and significant effect on PU. Furthermore, PEOU is also proven to have a positive and significant effect on BIU, while PU does not show a significant effect on BIU. These findings suggest that the ease of use of the e-learning system is the dominant factor in shaping students' interest in using e-learning continuously. The results of this research are expected to contribute theoretically to the development of technology acceptance studies in higher education and serve as a basis for practical recommendations for universities in designing and managing more effective, adaptive, and user-needs-oriented e-learning systems.